Commercialization of summer radish cultivation for higher income generation - Chaudhary, D. R.; Bhushan, Lav; Parmar, Sanjeev; Kumari, Manjula; Singh, Narinder; Murai, Ashish S.; Sheoran, Parvender (Indian Farming, 2025)
Under the ICAR’s Farmers FIRST Programme (2016–2024) in Dharer Panchayat, Baijnath Block, Kangra district, Himachal Pradesh, summer radish cultivation was promoted to enhance farmers’ income through diversification. Improved hybrids and scientific practices such as line sowing and seed treatment replaced traditional broadcast methods, resulting in higher yields (170.7 q/ha vs. 115.9 q/ha) and improved B:C ratios (4.9 vs. 2.8). Farmers adopted commercial-scale cultivation, supported by improved road access and market linkages. The intervention increased total farm income by about 79%, with nearly 45% of farmers doubling their income, demonstrating the profitability and scalability of summer radish in hill farming systems.